Examining Hessian fly (Mayetiola destructor) management concepts and quantifying the physiological impact of hessian fly feeding on post-vernalization selected cultivars of winter wheat in Kansas - Schwarting, Holly N. (Kansas State University, 2014)
The Hessian fly, Mayetiola destructor (Say), has been a historically significant pest of wheat in Kansas. However, it has been 60+ years since research has been conducted examining the flies’ activity throughout the year. Results of pheromone trapping in 4 counties in Kansas shows that Hessian fly (HF) males are actively flying in the fall, at least 1 month after the historical fly-free dates. Therefore, the Hessian Fly-Free Date is no longer valid and should be referred to as the Best Pest Management Date. Using pheromones for fall and spring trapping also indicated that HF is more active throughout the spring than previously thought, with almost continuous fly emergence and numerous emergence peaks in both spring and fall. The use of resistant wheat cultivars has been adapted to protect seedling plants from HF larval feeding in the fall. However, it is unknown if these cultivars are still providing protection after winter vernalization. Greenhouse trials indicated that ‘Armour’, a cultivar considered intermediately resistant, remains resistant under infestation levels of 1 fly/tiller but significant seed weight losses occured under infestations of 3 flies/tiller. In the field, Armour did not provide protection post-vernalization, with plants containing similar numbers of flaxseeds (pupae) as the susceptible cultivar, ‘Fuller’, and having significant losses of culm height (cm), number of spikelets/spike, number of seeds/spike, and seed weight (grams) when infested. ‘Duster’, a cultivar considered highly resistant, appeared to provide resistance to HF larval feeding in both the greenhouse and the field, and even produced significantly heavier seeds when infested with 3 flies/tiller in the greenhouse. These results suggest that post-vernalization screening should be conducted on all HF resistant cultivars to determine if each continues to provide protection. Little information is available showing if and how HF larval feeding on more mature wheat (Feekes 7-10), post-vernalization, impact plants, aside from lodging. Greenhouse and field infestations of a susceptible cultivar, Fuller, showed that significant losses of culm height (cm), number of seeds/spikelet, and seed weight will result from as few as 1 larva /culm. Yield losses averaged 0.13g/spike (65 kg/ha) compared to non-infested plants.
Keywords: Mayetiola destructor; Hessian fly; Plant resistance; Pheromone; Physiological impact; Winter wheat; Entomology (0353)